Model of the DGEBA-EDA Epoxy Polymer: Experiments and Simulation Using Classical Molecular Dynamics - Andreas Gavrielides; Thomas Duguet; Maëlenn Aufray; Corinne Lacaze-Dufaure (International Journal of Polymer Science)
Polyepoxy samples are synthesized from diglycidylether of bisphenol A (DGEBA) and ethylene diamine (EDA) monomers at a stoichiometric ratio of 2 DGEBA : 1 EDA in model conditions in order to promote a high degree of polymerization and a low density of defects and to try to approach the ideal models obtained by simulation. A slow polymerization (>24 h at ambient temperature) and a postcuring achieved in an inert atmosphere lead to a conversion degree of 92±2% and a midpoint glass transition temperature of 391±1 K. In parallel, a model is created with a multistep cross-linking procedure. In this work, all-atom molecular dynamics (MD) simulations are performed with LAMMPS and the GAFF 1.8 force field. In the initial liquid mixture of reactants (600 molecules), proper mixing is demonstrated by the calculation of the partial radial distribution functions (RDF), which show a minimum intermolecular distance of 2.8 Å and similar distributions for EDA-EDA, DGEBA-DGEBA, and DGEBA-EDA molecules in the simulation boxes. Then, in alternation with MD equilibrations, cross-linking is performed on frozen configurations by creating covalent bonds between reactive pairs within a reaction radius of 3 Å. The resulting boxes show conversion rates of 90-93% and densities close to the experimental value. Finally, a cooling ramp from 700 K to 25 K is applied in order to monitor the specific volume and the coefficient of volumetric thermal expansion (CVTE) of the polymer and to derive the glass transition temperature. Experimental thermomechanical analyses (TMA) compares well with simulations for both the specific volume and the CVTE evolutions with temperature. Whereas the uncertainty remains high with the fitting procedure used, we calculate a glass transition temperature of 390±8 K which compares very well with the experimental values (391±1 K from DSC and 380 K from TMA).